The Precautionary Principle and the Concept of Precaution. (1st November 2004) - Sandin, Per
The precautionary principle is frequently invoked in environmental law and policy, and the debate around the principle indicates that there is little agreement on what 'taking precautions' means. The purpose of the present paper is to provide an improved conceptual foundation for this debate in the form of an explication of the concept of precaution. Distinctions between precaution and two related concepts, prevention and pessimism, are briefly discussed. The concept of precaution is analysed in terms of precautionary actions. It is argued that precautionary actions are implicitly assumed to be precautionary with respect to something, and that this assumption should be made explicit. A definition of a precautionary action involving three necessary and jointly sufficient conditions (intentionality, uncertainty and reasonableness) is proposed, and the implications of this analysis for the debate on the precautionary principle are discussed.